Physical activity for adults and senior adults: The institutional program of Universidad de Costa Rica - Matamoros Sánchez, Maribel (2022)
The purpose of this article is to present the evolution of the Human Movement Module (HMM) of the IPSA and the impact this has had on the attention to senior adults (SA). The first university for senior adults originated in Toulouse, France, in the early 70’s, and it is thanks to Dr. Alfonso Trejos Willis that the Institutional Program for Adults and Senior Adults (IPSA) has existed for 35 years at Universidad de Costa Rica. Based on the premise of “education throughout life,” the University offers to Costa Rican citizens a valuable return in opening opportunities to this age group. Over time, the Program underwent a transformation in response to the needs and social changes of the Costa Rican population, in which the importance of keeping adults and senior adults active is expressed. As a result, the Human Movement Module (HMM) emerged, headed by facilitators that offer their courses pro bono. In this module, the courses were adapted to a virtual format in order to make them available to the senior adult population, a group that has been considered at risk due to the COVID-19 pandemic.